Test 'White's Reality Check' jako metoda weryfikacji automatycznych systemów transakcyjnych - Masłowski, Michał; Nowiński, Marek (Effectiveness' Verification of Mechanical Transactions Systems Using Whites's Reality Check, 2007)
The article presents a few methods of effectiveness' verification of mechanical transactions systems. These methods are divided into two parts. The first class of methods is based on assumption that different data are used to build and test system and different to verify its effectiveness. The second class of methods are based on bootstrap approach proposed by Brock [1992]. One of the variants of that method was proposed by White [2000] and is known as White's Reality Check test. This test is presented in details. The paper is exemplified by data from the Polish Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 154-162